Volcanic aerosol layers observed with multiwavelength Raman lidar over central Europe in 2008-2009 - Mattis, Ina; Siefert, Patric; Mueller, D.; Tesche, Matthias; Hiebsch, Anja; Kanitz, Thomas; Schmidt, Joerg; Finger, Fanny; Wandinger, Ulla; Ansmann, Albert (Journal of Geophysical Research, 2010)
In the framework of regular European Aerosol Research Lidar Network (EARLINET) observations, aerosol layers have been monitored with a multiwavelength aerosol Raman lidar in the upper troposphere and lower stratosphere over Leipzig (51.4 degrees N, 12.4 degrees E), Germany, since the summer of 2008. The origins of these layers are eruptions of different volcanoes on the Aleutian Islands, Kamchatka, Alaska, and on the Kuril Islands. FLEXPART transport simulations show that the volcanic aerosol is advected from Alaska to central Europe within about 7 days. The aerosol layers typically occurred in the upper troposphere above 5 km height and in the lower stratosphere below 25 km height. The optical depths of the volcanic aerosol layers are mostly between 0.004 and 0.025 at 532 nm. The wavelength dependence of the backscatter coefficients and extinction coefficients indicate Angstrom exponents from 1.0-2.0. Lidar ratios in the stratosphere are found in the range from 30-60 sr (355 nm) and 30-45 sr (532 nm). The estimation of the effective radius, surface-area, and mass concentrations of a volcanic aerosol layer, observed well within the stratosphere at end of August 2009, reveals values of 0.1-0.2 mu m, 5-10 mu m(2) cm(-3), and 0.3-0.5 mu g m(-3), respectively. Peer reviewed